Αρχιπέλαγος Γκουλάγκ, 1918-1956 - Solzhenitsyn, Aleksandr Isaevich, 1918-2008 (Σύγχρονοι κλασικοί συγγραφείς / Πάπυρος, 2009)
Αρχιπέλαγος Γκουλάγκ 1918-1956 Μέρη III-IV Αρχιπέλαγος Γκουλάγκ 1918-1956 Μέρη III-IV Κωδικός Λαβυρίνθου: 59959 Κωδικός-ISBN: 978960486 Έτος έκδοσης: 2013 Συγγραφέας: Solzhenitsyn, Aleksandr Isayevich, 1918-2008